Musulmans et non musulmans dans la Salonique ottomane (xviiie siècle).L’affrontement sur les espaces et les lignes de démarcation - Eyal Ginio (Revue des Mondes Musulmans et de la Méditerranée)
This paper explores the inter-communal relations in an Ottoman city – 18th century Salonica – against the background of recent studies that highlight the vitality of the urban public space and the ability of different religious and social groups to safeguard their interests vis-à-vis the rulers, to introduce their own agendas and to challenge existing social and physical boundaries. By using the evidence of the sicilt (the records of the şeriat court), I demonstrate the various legal strategies that were adopted by non-Muslims to secure their own interests in the public space: challenging existing boundaries or resisting any intrusion that might endanger their own position. My discussion evolves around three different places of encounter and conflict in Salonica: the prison, the Jewish cemetery and the neighbourhood. Finally, I assess the authorities’ response when facing such challenges: the local authorities often remained aloof when dealing with physical boundaries. However, whenever they suspected that religious boundaries were breached they reacted with vigour.